PENGARUH SERVICE QUALITY, PERCEIVED VALUE CORPORATE IMAGE, CUSTOMER SATISFACTION, PADA BEHAVIORAL INTENTION - JOSEPHINE ADELIA; KLEMENS WEDANAJI PRASASTYO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The Purpose on this study was to determine the effect of service quality, perceived value, corporate image, and customer satisfaction to behavioral intention. Statistical method using SEM (Structural Equation Modeling) with software WarpPLS and IBM SPSS as the tools. The research showed that interaction quality hadeffect to service quality, physical environment quality and outcome quality had no effect to service quality. Then service quality had effect to perceived value, corporate image and customer satisfaction. Perceived value and corporate image had effect to customer satisfaction. Then customer satsfaction and corporate image had effect to behavioral intention. The ultimate goal of this study so that company can find out the factors that must be improved.